Estado nutricional avaliado pela mini avaliação nutricional como fator prognóstico de mortalidade em pacientes idosos com câncer - Erika Simone Coelho Carvalho (2023)
Introduction: Malnutrition in older patients can increase mortality, length of hospital stay, worsen quality of life, as well as reduce tolerance to oncologic therapy and increase therapyrelated toxicity. The mini nutritional assessment (MNA) tool is practical and non-invasive, allowing a quick assessment of the nutritional status of the older patients. The mini nutritional assessment (MNA) tool is practical and non-invasive, allowing a quick assessment of the nutritional status of the elderly. In the short form of the MNA (MNA-SF), when there is no body mass index (BMI), calf compression is used (CC < 31 cm). In Brazil, the calf circumference (CCBR) has a cutoff point for men (CCBR ≤ 34 cm) and for women (CCBR e ≤33 cm). Objective: To evaluate MNA-SF as a predictor of risk of death in older patients with cancer. Methods: This is a multicenter, descriptive, and prospective study, which included all older female or male patients, aged 60 years or older, with malignant tumors, regardless of location or stage of the disease, hospitalized in Brazilian/Portuguese institutions from September to December 2014. Results: We evaluated 2677 older patients with cancer, 56.4% of whom were male. The mean age was 73 ± 6.7 years. The patients had the digestive system, prostate and skin as the main tumor locations (56.9%) and 9% died during the period of hospitalization and follow-up of the study. Four MNA-SF models were tested to predict mortality in the older patients with cancer. The areas of the models on the ROC analyzes ranged from 0.79 to 0.80, with the reference being the original model (MNA-SFBMI/CC). Statistical analysis showed similar curves, but with a significant difference for the MNA-SFIMC/CCBR model (MNA-SF classification, where BMI or CCBR scores were used). In the adjusted model, there was a greater chance of death among older patients with “severe loss of appetite”, “reduced mobility” (being greater in those “restricted to bed”) and with “neuropsychological problems”. When considering the MNA-SF scores, patients with a score lower than eight in its original version (MNA-SFBMI/CC) or using MNA-SFBMI/CCBR, had a higher risk of death. It also showed that the MNA-SF could be used to identify risk of mortality with a score lower than six, without considering the score for anthropometry (BMI or CC). Conclusion: The proposed MNA-SFBMI/CCBR model proved to be the best predictor of mortality in older patients with cancer. The MNA-SF was able to predict risk of death, even without measuring BMI or CC, while the addition of anthropometry did not improve the recognition of malnutrition or mortality risk in older patients with cancer.